Rodent and Flea Abundance Fail to Predict a Plague Epizootic in Black-Tailed Prairie Dogs - Brinkerhoff, Robert Jory (Mary Ann Liebert, Inc., 2010)
Small rodents are purported to be enzootic hosts of Yersinia pestis and may serve as sources of infection to prairie dogs or other epizootic hosts by direct or flea-mediated transmission. Recent research has shown that small rodent species composition and small rodent flea assemblages are influenced by the presence of prairie dogs, with higher relative abundance of both small rodents and fleas at prairie dog colony sites compared to grasslands without prairie dogs. However, it is unclear if increased rodent or flea abundance predisposes prairie dogs to infection with Y. pestis. We tracked rodent and flea occurrence for 3 years at a number of prairie dog colony sites in Boulder County, Colorado, before, during, and after a local plague epizootic to see if high rodent or flea abundance was associated with plague-affected colonies when compared to colonies that escaped infection. We found no difference in preepizootic rodent abundance or flea prevalence or abundance between plague-positive and plague-negative colonies. Further, we saw no significant before-plague/after-plague change in these metrics at either plague-positive or plague-negative sites. We did, however, find that small rodent species assemblages changed in the year following prairie dog die-offs at plague-affected colonies when compared to unaffected colonies. In light of previous research from this system that has shown that landscape features and proximity to recently plagued colonies are significant predictors of plague occurrence in prairie dogs, we suggest that landscape context is more important to local plague occurrence than are characteristics of rodent or flea species assemblages.